94 The Effects of Weather, Body Weight, and Dry Matter Intake on Total Daily Water Intake in Beef Steers. (8th October 2021) - McDaniel, Zach S; Smith, Zachary K; Wright, Cody; Gonda, Michael; Wickremasinghe, Himali; Djira, Gemechis
Abstract: Weaned angus steers (n = 26; 272.92 + 21.29 kg) were selected to study the effects of weather, predicted daily BW, and DMI on total daily water intake (TDWI) from December 2019 to May 2020 (181 days). Calves were provided with ad libitum access to feed and water, under a monoslope barn, for the duration of the study. In periods of cold stress, cattle were provided with corn stalk bedding within the dry lot, away from the monoslope barn. Measurements of feed and water disappearance were obtained by utilizing an automated feed and water system (Insentec RIC, Hokofarm, Marknesse, Netherlands), where disappearance was assumed to be caused by intake. Calves were weighed every 28 days in order to calculate ADG and therefore predict daily BW for each calf. Daily weather records, including windchill (°C), solar radiation (W/m 2 ), and maximum relative humidity (%), were obtained through the South Dakota Mesonet automated weather station located 3.86 km from where the calves were housed. A linear mixed effects model with both random intercept and slope were used to account for the within subject correlations. Increased TDWI was associated with increased wind chill (0.38-kg per 1°C; P < 0.0001), increased solar radiation (1.04-kg per 1 W/m 2 ; P < 0.0001), and decreased maximum relative humidity (-0.14 kg per 1%; P < 0.0001). For every kg increase in DMI, TDWI increased by 1.07 kg (P < 0.0001). Lastly, for every kg increase in BW, TDWI increased by 0.05 kg (P < 0.0001). Effects of DMI, BW, SRAD, windchill, RHMax were predictive of TDWI in beef calves fed during the winter. This model will be useful for predicting TDWI during the winter months where calves are raised in regions where temperatures are regularly below freezing.